Risk Factor Analysis of Family Characteristics and Health History of Children Under Five on the Incidence of Stunting in Sidenreng Rappang, South Sulawesi, Indonesia - Zulkarnain Sulaiman; Devy Febrianti; Sunandar Said; Khaeriyah Adri (Journal of Epidemiology and Public Health, 2021)
Backround: Stunting was one of the global nutritional problems that are still widely found, especially in developing countries. in Asia, 87 million children were stunted. This study aimed to look at the risk of family characteristics and health history on the incidence of stunting.Subjects dan Method: This was a case-control study conducted in the Sidenreng Rappang district. The dependent variables were family characteristics consisting of maternal education and household members and health history consisting of LBW and infectious diseases. The inde